Advances in the progress of monoclonal antibodies for rabies. Issue 1 (31st December 2022) - Fan, Linlin; Zhang, Li; Li, Jingxin; Zhu, Fengcai
ABSTRACT: Rabies is a highly fatal zoonotic disease caused by the rabies virus invading the central nervous system. When suspected of exposure to the rabies virus, post-exposure prophylaxis should be administered as soon as possible. Monoclonal antibodies (mAbs) neutralizing the rabies virus could be better in human rabies post-exposure prophylaxis than equine or human rabies immune globulin in terms of supply, cost, and efficacy. This article reviews anti-rabies mAbs produced by multiple techniques, and the results of clinical trials for anti-rabies mAbs cocktails recognizing non-overlapping epitopes are also discussed.